COINCIDENCE AND DIFFERENCE OF AGREED ATTRIBUTE IN COMPOUND LITHUANIAN, LATIN AND ENGLISH ANATOMICAL TERMS - Litevkienė, Nijolė; Briedytė, Jurgita (PROFESSIONAL STUDIES: Theory And Practice, 2022)
It can be said that the anatomical terminology is a specific collection of scientific terms. One of the major flaws in early anatomical terminology was that body structures were described by varying names, while some of the terms were irrational in nature and confusing. At this time, different international committees were working on preparing a unified final version of the anatomical terminology. Each country wanted to have its own nomenclature. To this end, each country based its nomenclature on the international anatomical terminology, and then translated it into its own language. According to Sakai (2007) the historical development of anatomical terminology – the oldest layer of medical terminology – can be divided into five stages: colloquial Greek words of that period used by Galen as anatomical terms; terms from the early 16th century, when Vesalius described the anatomical structures in his De humani corporis fabrica; terms from the late 16th century when Sylvius in Paris and Bauhin in Basel described muscles, vessels and nerves; terms from the 17th-19th century when anatomical textbooks were written in Latin and later in other modern languages; terms from the end of 19th century, when the first international anatomical terminology in Latin was published as Nomina Anatomica. Keywords: English medical terminology, Latin medical terminology, Lithuanian medical terminology, aspects of medical terminology